Latent Anti-nutrients and Unintentional Breeding Consequences in Australian Sorghum bicolor Varieties - Hodges, Hayden E.; Walker, Heather J.; Cowieson, Aaron J.; Falconer, Robert J.; Cameron, Duncan D. (Frontiers in Plant Science, 2021)
Modern feed quality sorghum grain has been bred to reduce anti-nutrients, most conspicuously condensed tannins, but its inclusion in the diets of monogastric animals can still result in variable performance that is only partially understood. Sorghum grain contains several negative intrinsic factors, including non-tannin phenolics and polyphenols, phytate, and kafirin protein, which may be responsible for these muted feed performances. To better understand the non-tannin phenolic and polyphenolic metabolites that may have negative effects on nutritional parameters, the chemical composition of sorghum grain polyphenol extracts from three commercial varieties (MR-Buster, Cracka, Liberty) was determined through the use of an under-studied, alternative analytical approach involving Fourier-transform infrared (FT-IR) spectroscopy and direct ionization mass spectrometry. Supervised analyses and interrogation of the data contributing to variation resulted in the identification of a variety of metabolites including established polyphenols, lignin-like anti-nutrients, and complex sugars, as well as high levels of fatty acids which could contribute to nutritional variation and underperformance in monogastrics. FT-IR and mass spectrometry could both discriminate among the different sorghum varieties indicating that FT-IR, rather than more sophisticated mass spectrometric methods, could be incorporated into quality control applications.